2019
DOI: 10.1101/748756
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Face Selective Neural Activity: Comparison Between Fixed and Free Viewing

Abstract: AbstractEvent Related Potentials (ERPs) are widely used to study category-selective EEG responses to visual stimuli, such as the face-selective N170 component. Typically, this is done by flashing stimuli abruptly at the point of static gaze fixation. While allowing for good experimental control, these paradigms ignore the dynamic role of eye-movements in natural vision. Fixation-related potentials (FRPs) obtained using simultaneous EEG and eye-tracking, overcome this limitation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 93 publications
2
4
0
Order By: Relevance
“…This depletion might override the negative effect of the source usually associated with the N170, which in turn will lead to a generally more positive activation. This amplitude reduction is in line with previous studies (Auerbach-Asch et al, 2019; Buonocore et al, 2020). Notably, the fERP in our study is changing earlier than previously reported (Schweinberger & Neumann, 2016).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…This depletion might override the negative effect of the source usually associated with the N170, which in turn will lead to a generally more positive activation. This amplitude reduction is in line with previous studies (Auerbach-Asch et al, 2019; Buonocore et al, 2020). Notably, the fERP in our study is changing earlier than previously reported (Schweinberger & Neumann, 2016).…”
Section: Discussionsupporting
confidence: 94%
“…As the combination of these two aspects is what we encounter in our everyday life, it is necessary to combine them to obtain the full picture of naturalistic face perception. Not only are we able to confirm results classically reported in passive perception experiments (Rossion & Jacques, 2008), but we also replicate the findings of one of the first studies combining free viewing and face perception (Auerbach-Asch et al, 2019) comparing fERPs recorded during task-driven free viewing to ERPs in a passive stimulation task using cutout faces. Yet, we could demonstrate that naturalistic face processing will lead to earlier effects, including time points classically defined as the P100, and extend beyond parieto-occipital electrodes, throughout the whole scalp.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations